Relación entre la incorrecta aplicación del principio in dubio pro reo y la impunidad de delitos en procesos ordinarios - Viñas Adrianzén, Carmen Ruth (2017)
This research work had as main objective to clarify the relationship of the principle of dubio pro reo and impunity from prosecution in ordinary proceedings in the Judicial District of La Libertad, in years two thousand three-two thousand and four. This was done for a study of the sets of ordinary sentences in which it has applied the principle in dubio pro reo, checked the way it has applied the principle in words, making use for this analysis methodology -- synthesis, which enabled a comprehensive study of the problem to an effective investigation. For which information was collected from the three Chambers Criminal Justice Superior Court of Liberty, finding that the First Criminal Court applied the principle in dubio pro reo the year two thousand three and thirteen year processes in twenty- two thousand and four processes, the Second Criminal Division in the year two thousand three, and seven processes in the two thousand four in fourteen, the Third Criminal Division in the year two thousand and three in fourteen processes and in the year two thousand four into eight processes. From the investigation it is concluded that the misapplication of the principle of dubio pro reo generates impunity for crimes.